(3TQM GdeLehY GdcdGFjs - (3OGhO Hf SdjeGf Hf MSf Hf YHjO Gddg, GHf CHj GdQHjY GdHfHj GdeYQha H CHj GdLhO,J (B863 (3g` s ((3ehSi Hf QLH GdUQNOi s)
(3ChdgG (B:s
(3CeG HYO abO SCdfi HYV ENhGfi GdabQGA GdUGdMjf GdeTJZdjf HGdYdhe GdESdGejI Cf CcJH eNJUQ ehVMkG aUd ai ebOeGJ gPG Gdaf ef GdCUhd s
(3BNQgG (B:s
(3bhdg hjHbi CSge SJ gj GdHGbjI JYO HYO fUjH GdSGbj hbO TQM GdeUfa QMeg Gddg JYGdi GdeSFdI TQMkG cGajkG aJCedg hGddg CYde Je GdcdGe Ydi TQM GdeLehY s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B332 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B137s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs